Regional Archives in the Ottoman Period - Aktaş, Necati (Prilozi za orijentalnu filologiju, 2017)
Regional authority institutions in the Ottoman state which were in permanent communication with the central bureaucracy tried to keep pace with the work of the central authority in the systematic keeping of documentation. Regional authorities had to keep official documents according to a specified method and an ordered format. Those documents were both an inflow of information from the central authority, and the results of work at local level. In the period prior to the Tanzimat, the quadi was the main centre of regional authority, and for that reason those documents were included in the quadi or Shari.a sigils . court records. Those sigils were the foundation for the regional archive administration. Along with the court cases decided on before the quadi, transcripts of various documents were also recorded in them, such as vakufnamas . deeds of perpetual endowment, testaments, sales documents, indebtedness, as well as orders, charters and other official documents. Along with that, eyalet and sanjak archives were established in the regions. In those archives they kept defters - public records in which they entered decisions of local authorities and orders coming in from higher instances. The central authority took strict account that such archives should be kept in a systematic way and continually, and they issued orders thereon. Regretfully, the majority of those regional Ottoman archives were destroyed, especially in the post-Ottoman period in wars, fires, disasters, or simply due to human neglect. This happens in our time as well. Such an example is the complete destruction of the collections of the Institute for Oriental Studies in 1992, caused by an incendiary shell fired from the Serb positions around Sarajevo. Nevertheless, a number of Ottoman documents, very important for the study of both local history and the history of the Ottoman Empire as a whole, are still kept in archives, museums and other institutions in the countries that used to be under the rule of the Ottoman Empire.